Development And Evaluation Of A Culturally-Specific Diabetes Self-Management Education And Support Programme For Type 2 Diabetes Mellitus Patients In Baghdad, Iraq: A Mixed-Method Study - Mikhael Al-Alchy, Ehab Mudher (2022)
Most Iraqi patients with type 2 diabetes (T2DM) do not achieve the glycemic target due to the lack of available diabetes self-management education and support (DSME(S)) programs. The current study aimed to explore the knowledge and practice of T2DM patients at the National Diabetes Center, Baghdad, Iraq towards diabetes self-management (DSM) behaviors; besides, developing culturally-specific tools to assess DSM, medication adherence, and quality of life (collectively, DMAQ) along with the development of a culturally-based DSME(S) program and evaluating its benefits and cost-effectiveness.